Regioselectivity in nucleophilic ring-opening of aziridinones - M. M., Yusoff; Talaty, Erach R. (Royal Society of Chemistry, 1998)
The proportions of products derived from competing modes of ring-opening of 1,3-di-tert-butylaziridinone and similar aziridinones by a variety of nitrogen, oxygen, sulfur and halogen nucleophiles do not agree with simple guidelines postulated in the literature for these types of aziridinones.